2021
DOI: 10.1016/j.scitotenv.2021.149505
|View full text |Cite
|
Sign up to set email alerts
|

Drought risk for agricultural systems in South Africa: Drivers, spatial patterns, and implications for drought risk management

Abstract: The regular drought episodes in South Africa highlight the need to reduce drought risk by both policy and local community actions. Environmental and socioeconomic factors in South Africa's agricultural system have been affected by drought in the past, creating cascading pressures on the nation's agro-economic and water supply systems. Therefore, understanding the key drivers of all risk components through a comprehensive risk assessment must be undertaken in order to inform proactive drought risk management. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Of all economic sectors, the agriculture sector is arguably the most affected by drought (Matlou et al, 2021). In South Africa, the agriculture sector is dual comprising of the smallholder and commercial sub-sectors, which have varying vulnerabilities and responses to drought (AgriSETA, 2020a; Meza et al, 2021). The smallholder sub-sector is more vulnerable to drought largely due to lack of adaptive capacity, poor governance, and lack of availability of relevant knowledge and skills on drought management among farmers and agricultural professionals (Terblanché, 2013; Baudoin et al, 2017).…”
Section: Effects Of Drought On Agricultural Skills In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Of all economic sectors, the agriculture sector is arguably the most affected by drought (Matlou et al, 2021). In South Africa, the agriculture sector is dual comprising of the smallholder and commercial sub-sectors, which have varying vulnerabilities and responses to drought (AgriSETA, 2020a; Meza et al, 2021). The smallholder sub-sector is more vulnerable to drought largely due to lack of adaptive capacity, poor governance, and lack of availability of relevant knowledge and skills on drought management among farmers and agricultural professionals (Terblanché, 2013; Baudoin et al, 2017).…”
Section: Effects Of Drought On Agricultural Skills In South Africamentioning
confidence: 99%
“…Ex-post crisis management, normally undertaken by the government, is characterised by crisis identification resulting in provision of post-drought relief or assistance to the most affected individuals and areas (Shiferaw et al, 2014). This is usually costly, bureaucratic, poorly coordinated, implemented late and focuses on immediate needs rather than pre-emptively improving resilience towards possible future droughts (Meza et al, 2021; Ngaka, 2012). Ex-ante risk management (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To calculate ETa, ETo was first computed by applying the Global Crop Water Model (GCWM) using the FAO-PM method [50] and hourly ERA5-reanalysis data with 0.25 degrees spatial resolution aggregated to daily climate input. The model was executed in daily time steps with a spatial resolution of 5 arc-minutes (about 8 Km) [51]. Statistical analysis and visualization of the results were conducted in R [52] and QGIS [53].…”
Section: Localization Of Modis-based Evi(evi2) and Etamentioning
confidence: 99%
“…A conceptual framework combining integrated landscape management (ILM) and institutional design principles (IDP) perspectives was applied to analyze cooperation initiatives involving water suppliers and agricultural stakeholders from agricultural wastewater 5 . A national drought risk assessment for agricultural lands taking into account the complex interaction between different risk components was presented 40 . The research showed that crop diversification, crop pattern management, and conjunctive (i.e., surface water and groundwater) water management can be effective in improving agricultural water 18 , 48 .…”
Section: Introductionmentioning
confidence: 99%